Site use by non-breeding Black-tailed Godwits at Nijhum Dweep National Park, Bangladesh - Das, D.K.; Khandakar, N.; Sultana, I.; Islam, S.; Ali, M.S.; Galib, A.J.; Shamsuddoha, M.; Piersma, T. (Wader Study, 2022)
The Black-tailed Godwit Limosa limosa is a globally Near Threatened species but a common winter visitor to Bangladesh. Although the total wintering population size and trend are unknown, we suspect it is declining due to habitat degradation. Nijhum Dweep National Park is one of the most important sites for Black-tailed Godwits in Bangladesh. Here we report on the site use of Black-tailed Godwits in this national park and adjacent Char Birbira. From October to March 2016–2017 to 2019–2020, we performed 17 winter counts. High-tide roosts were counted from vantage points in these tidal areas, whereas foraging activities were observed from boats during low tide. Black-tailed Godwits were always present, with counts ranging from 735 in January 2020 to 8,269 in December 2017 with a mean of 3,304. The uncertainty of these counts and population estimates for this area in general suggest that better assessment methods, such as simultaneous high-tide counts undertaken at the same time each year, are needed. Our study area met the Ramsar 1% threshold population criterion for the species for 13 of the 17 counts, demonstrating the international importance of this area for Black-tailed Godwits. A local decline of >80% from 9,000 to 1,707 birds over the last decade was apparent on Damar Char West. Over the decades, the landscape of Damar Char has changed, with increased numbers of households, more land converted to agricultural fields, and increased fishing effort. These changes call for better assessments of bird movements and disturbance and more effective conservation actions to help birds and people coexist. We suggest that there should be a monitoring and protection scheme in the Nijhum Dweep management plan that focuses on waterbirds, and restricts and regulates access to Damar Char West, East and Char Birbira. An urgent attempt to create awareness among the main stakeholders, fishers and crab hunters, to provide context and engage them in conservation action, should be a priority.